Scale morphologies of freshwater fishes at Tembat Forest Reserve, Terengganu, Malaysia - Farah Ayuni Farinordin,; Wan Seribani Wan Nilam,; Shahril Mod Husin,; Abdullah Samat,; Shukor Md. Nor, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Scales are calcium carbonate and collagen-contained structures embedded within the fish epidermis and useful for species identification. This study aimed to describe morphological characteristics of scales and use the differences to prepare keys to species. Fishes were sampled from selected rivers of Tembat Forest Reserve, Hulu Terengganu. Specimens caught were from 3 families (Cyprinidae, Channidae, Nandidae) and 17 species. Each species was represented by ten individuals (size ranges 2.5 - 50 cm TL). The scales were removed, soaked in H2O2 (0.5%), NH3 (0.3%), DH2O and mounted between a pair of glass slides for digital photographing. The morphological descriptions were based on types of scales, distinctiveness of radii arrangement at the anterior field, radii cover, radii distribution, overall shape, focus position and focus pattern. Keys to species were constructed based on these scale morphological characters described. Measurements of scale total length (L), total width (W), rostral field length (L1) and caudal field length (L2) of the scales were taken using Image J software. The inter-specific variation among scales was indicated by L1/L, L2/L, L1/L2 and W/L indices through multiple comparison tests (ANOVA). It was found that all 17 species showed significant differences with at least one other species in all four indices. Pristolepis grootii (Bleeker 1852) was the only one that significantly different (p<0.05) from other 16 species in the first three indices. Species that showed the least significant differences among species was Probarbus jullieni (Sauvage 1880). The differences among the scales were primarily due to the different types of scale that was either ctenoid or cycloid.